The Worst Hard Time: The Untold Story of Those Who Survived the Great American Dust Bowl - Courtney Meyers (Journal of Applied Communications, 2013)
Book review: The Untold Story of Those Who Survived the Great American Dust Bowl by Timothy Egan
Keywords: Worst; Hard Time; Dust Bowl